Asuhan Keperawatan Klien yang Mengalami Gangguan Rasa Nyeri dengan Post Op Apendisitis di RSUD Budhi Asih Jakarta - Amalia Septiana Dewi; Restu Iriani (Jurnal Persada Husada Indonesia, 2020)
Nursing care for clients with post op appendicitis is a series of nursing process in overcoming the problem on the clients. Appendicitis is an inflammation of the appendix vermiformis and is the most common cause of acute abdomen. Nursing care is done to prevent and reduce mortality in the future. Based on the medical records obtained results of 11 clients in the West Emerald Room recorded the diagnosis of post op appendicitis at Regional Public Hospital Budhi Asih in January, February, and March 2018. In this case, thestudy aims to carry out nursing care on clients who experience acute pain with post op appendicitis in Regional Public Hospital Budhi Asih. In this scientific paper used qualitative research methods, descriptive, case study approach with intervention is reduced pain. Participants in this case study included clients, families, and nurses. Subjects who used 2 clients with the same medical diagnoses and nursing problems of clients who experienced acute pain with post op appendicitis, 2 families, and 2 nurses room. Characteristics of participants in this case study included male and female clients and had post-op wound pain. The results showed priority nursing diagnoses on acute pain clients with post-op appendicitis performed nursing actions of deep breathing relaxation techniques and distraction techniques. Evaluation of acute pain nursing problems associated with post-op appendicitis in both clients is resolved, pain decreases with the pain scale 1-2 and the clients appears relaxed.